Role of extracellular matrix structural components and tissue mechanics in the development of postoperative pancreatic fistula. (9th November 2021) - Schmuck, Rosa B.; Lippens, Evi; Wulsten, Dag; Garske, Daniela S.; Strönisch, Annika; Pratschke, Johann; Sauer, Igor M.; Duda, Georg N.; Bahra, Marcus; Cipitria, Amaia
Abstract: Radical resection remains the only curative treatment option in pancreatic cancer. Postoperative pancreatic fistulas (POPF) occur in up to 30% of patients leading to prolonged hospital-stay, increased cost of care and morbidity and mortality. Mechanical properties of the pancreas are associated with POPF. The aim of this study is to analyze the role of extracellular matrix (ECM) and tissue mechanics in the risk of POPF. Biopsies of 41 patients receiving a partial pancreas-resection are analyzed. Clinical data, ECM components and mechanical properties are correlated with POPF. Preoperative cholestasis is correlated with reduced risk of POPF, which comes along with a dilatation of the pancreatic duct and significantly higher content of collagen I. Patients developing POPF exhibited a degenerated tissue integrity, with significantly lower content of fibronectin and a trend for lower collagen I, III, IV and hyaluronic acid. This correlated with a soft tactile sensation of the surgeon during the intervention. However, this was not reflected with tissue mechanics evaluated by ex vivo uniaxial compression testing, where a significantly higher elastic modulus and no effect on the stress relaxation time were found. In conclusion, patients with cholestasis seem to have a lower risk for POPF, and an increase in collagen I. A degenerated matrix with lower content of structural ECM components correlates with increased risk of POPF. However, ex vivo uniaxial compression testing failed to clearly explain the link of ECM properties and POPF.